911 in plane site the director's cut - Vonkleist, Dave; Lewis, William; Power Hour Productions; Bridgestone Media Group ([Missouri] : Power Hour Productions, 2004)
A documentary that presents the video evidence on attack to Pentagon and World Trade Center (WTC)
PAL format
Produced and written, Dave Vonkleist ; music and directed, William Lewis
Host : Dave Vonkleist
Keywords: September 11 Terrorist Attacks, 2001; Terrorism -- United States; American Airlines Flight 77 Hijacking Incident, 2001